Empowering “Girli” batik craftswomen to enhance family economy and develop tourism village in Sragen District / Slamet Supriyadi and Sariatun - Supriyadi, Slamet; Sariatun, Sariatun (2016)
This research which underlines several issues concerning the empowerment of “Girli” batik craftswomen in Sragen District was generally aimed at formulizing strategies to empower “Girli” batik craftswomen in Sragen District. The method which is used in the first step of this study is explorative study to some potency which is related to Girli in Sragen District. The data were collected from primary and secondary sources. Primary sources involved the informant such as Batik businessman, the artist, the leaders of Kliwonan and Pilang village , the officials of Diperidag (Dinas Perindustrian dan Koperasi). The data were collected by deep interview, observation, and document analysis. To make the data become valid the technique which is used is called triangulation of data. Interactive model analysis is used to analyze the data. The results show that there are several strategies to empower “Girli” batik craftswomen, they are: (1) improving the capacity of batik of the craftswomen so that they are able to get better status, from craftswomen becoming enptrepreneurs; (2) improving the competency of “Girli” batik craftswomen in Sragen District so that they are able to increase the quality and competitiveness of the batik products; (3) strengthening the networks and partnerships with various stakeholders including the private sectors, government and society; (4) facilitating the promotion and enhancing marketing networks; (5) building institutional system which takes sides to “Girli” batik craftswomen; (6) improving business management; (7) providing support on working-capital in a form of soft loan; (8) providing technical supervision in a form of training and mentoring; and (9) increasing the quantity and quality of access and transportation.